The brain and reading - D'Arcangelo, Marcia; Wurzburg, Gerardine ([S.l.] : Association for Supervision and Curriculum Development, 1999)
Highlights on the process of learning and reading in the elementary and high schools
Part 1. Making connections - Part 2. Strategies for elementary school - Part 3. Strategies for high school
Editor, Patty Stern ; writer, Marcia D' Arcangelo
Narrator: Franchelle Dorn
Keywords: Reading -- Study and teaching; Reading (Primary); Reading (Seconday); Reading (Elementary)